Exploring of gut microbiota features in dyslipidemia and chronic coronary syndrome patients undergoing coronary angiography - Luangphiphat, Wongsakorn; Prombutara, Pinidphon; Muangsillapasart, Viroj; Sukitpunyaroj, Damrong; Eeckhout, Eric; Taweechotipatr, Malai (Frontiers in Microbiology, 2024)
Chronic coronary syndrome (CCS) has a high mortality rate, and dyslipidemia is a major risk factor. Atherosclerosis, a cause of CCS, is influenced by gut microbiota dysbiosis and its metabolites. The objective of this study was to study the diversity and composition of gut microbiota and related clinical parameters among CCS patients undergoing coronary angiography and dyslipidemia patients in comparison to healthy volunteers in Thailand. CCS patients had more risk factors and higher inflammatory markers, high-sensitivity C-reactive protein (hs-CRP) than others. The alpha diversity was lower in dyslipidemia and CCS patients than in the healthy group. A significant difference in the composition of gut microbiota was observed among the three groups. The relative abundance of Proteobacteria, Fusobacteria, Enterobacteriaceae, Prevotella, and Streptococcus was significantly increased while Roseburia, Ruminococcus, and Faecalibacterium were lower in CCS patients. In CCS patients, Lachnospiraceae, Peptostreptococcaceae, and Pediococcus were positively correlated with hs-CRP. In dyslipidemia patients, Megasphaera was strongly positively correlated with triglyceride (TG) level and negatively correlated with high-density lipoprotein cholesterol (HDL-C). The modification of gut microbiota was associated with changes in clinical parameters involved in the development of coronary artery disease (CAD) in CCS patients.